2016
DOI: 10.1186/s12906-016-1132-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drying on the bioactive compounds, antioxidant, antibacterial and antityrosinase activities of pomegranate peel

Abstract: BackgroundThe use of pomegranate peel is highly associated with its rich phenolic concentration. Series of drying methods are recommended since bioactive compounds are highly sensitive to thermal degradation. The study was conducted to evaluate the effects of drying on the bioactive compounds, antioxidant as well as antibacterial and antityrosinase activities of pomegranate peel.MethodsDried pomegranate peels with the initial moisture content of 70.30 % wet basis were prepared by freeze and oven drying at 40, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
83
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(115 citation statements)
references
References 69 publications
(78 reference statements)
8
83
1
3
Order By: Relevance
“…On the other hand, drying process caused a decrease in gallic acid content of both Hicaznar (ranging from 111.232 mg/100 g to 45.313 mg/100 g) and 33 N 16Keben (varied from 66.036 mg/100 g to 52.737 mg/100 g) in comparison with control samples. The reduction of quantities of phenolic compounds during drying processes has also been observed in different studies (Mphahlele et al, ; Tontul & Topuz, ). It was observed statistically significant differences among phenolic compounds of Hicaznar pomegranate arils compared to control group ( p < 0.05).…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…On the other hand, drying process caused a decrease in gallic acid content of both Hicaznar (ranging from 111.232 mg/100 g to 45.313 mg/100 g) and 33 N 16Keben (varied from 66.036 mg/100 g to 52.737 mg/100 g) in comparison with control samples. The reduction of quantities of phenolic compounds during drying processes has also been observed in different studies (Mphahlele et al, ; Tontul & Topuz, ). It was observed statistically significant differences among phenolic compounds of Hicaznar pomegranate arils compared to control group ( p < 0.05).…”
Section: Resultssupporting
confidence: 55%
“…Dried pomegranate peel contains phenolic acid (p‐coumaric), flavan‐3‐ols (+catechin,‐epicatechin), flavanone (hesperidin), flavonol (rutin), ellagitannin (punicalin) (Mphahlele, Fawole, Makunga, & Opara, ). Punicalin values of pomegranate peel changed between 559.60 and 888.40 mg/kg dw (Mphahlele et al, ), and punicalin is hydrolyzable tannin which is known to account for high antioxidant activity in pomegranate peel (Lin, Hsu, Lin, & Hsu, ; Sun, Tao, Men, Xu, & Wang, ; Tzulker et al, ). In another study, pomegranate juice contained 22.8 ± 0.69 μg/100 g vitamin A, 57.8 ± 0.59 mg/100 g vitamin C, and 0.07 ± 0.01 mg/100 g vitamin E (Anahita, Asmah, & Fauziah, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lowering the microwave power to the lowest level at 180 W caused an even higher reduction in the content of individual value. It has been observed that the high porosity of dehydrated products promotes greater contact of the material with oxygen, which makes the released antioxidants more prone to oxidative damage (Mphahlele et al, ). Carrying out drying at 180 W increased the required drying time by ∼50% compared to that at 300 W, which increased the exposure to oxygen and oxidative enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, proper drying methods are essential to preserve the cellular metabolites in harvested seaweed thalli. In food processing, freeze drying is commonly used to capture phenolic, tannin, and flavonoid compounds in the food (Mphahlele, Fawole, Makunga, & Opara, ). However, freeze drying is expensive and the drying capacity is smaller than for shade‐, sun‐, and oven‐drying.…”
Section: Discussionmentioning
confidence: 99%